(untitled) (Journal of Politics and International Studies, 2025)
The development of sovereignty as a core concept in International Relations is one of the most important developments of Westphalia revolution. Promoted by International Law and United Nations Charter, the sanctity of sovereignty has received its loudest support. However, the realization of interdependence of human society has again produced a world community with codes, ethics, norms and morality for securing peace. The adoption in 2005 of R2p at the World Summit sounded largely that the world is a community that places high premium on the idealism of world peace and security to the detest of dictatorship. Thus in Libya, the sanctity of R2P rose to secure the responsibility of sovereignty to protect the Libyan population while reversely; it has failed to act in Syria. While some put this failure at the doorstep of Syrian powerful friends, others argue that R2p implementation in Libya has given it a bad name. It is in this contest that the argument is situated, using idealism as prime plank for analyzing the failure of the International Community to act in the crisis that has snowballed into a civil war and the resurgence of a Second Cold War amongst the great powers.